ChemInform Abstract: Asymmetric Henry Reaction of Trifluoromethyl Ketone and Aldehyde Using Cu(II)‐Complex: Computational Study Offers the Origin of Enantioselectivity with Varied Size of Catalysts. Issue 46 (November 2015) - Das, Anjan; Choudhary, Manoj K.; Kureshy, Rukhsana I.; Jana, Kalyanashis; Verma, Shailesh; Khan, Noor‐ul H.; Abdi, Sayed H. R.; Bajaj, Hari C.; Ganguly, Bishwajit
Abstract Four new 1, 2‐diphenylethylenediamine‐based ligands are synthesized and evaluated in the Cu(II)‐catalyzed title reaction.